PENGARUH PENGGUNAAN DOMPET DIGITAL TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA UNIVERSITAS HKBP NOMMENSEN MEDAN - Gea, Silvia Decmerry Natalia; Waruwu, Poppy Efrida; Siagian, Nalom (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This research focuses on the use of digital wallets among students at HKBP Nommensen University, Medan. With the aim of knowing whether there is an effect of using digital wallets on consumptive behavior in HKBP Nommensen University Medan Students. This study uses a quantitative approach with a causal associative method. The population in this study were even semester 2020/2021 students at HKBP Nommensen University Medan with a total sample of 99 respondents. In this study the sampling technique used the Sample Probability method with the Proportionate Stratified Random Sampling type. Data collection was carried out using a questionnaire distributed via Google Form. The results of this study indicate that the use of digital wallets has a positive and significant effect on consumer behavior among students at HKBP Nommensen University Medan.